ASSESSMENT INFLUENCE OF WIND ON REALIZATION AND SAFETY OF MILITARY AVIATION FLIGHTS IN «ARZNI» AIRDROME REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The winds blowing in the «Arzni» airdrome area are observed in the article. It is found out that during year in the first half of the day Northern (20%), Northeast (14%) winds prevail and in the second half of the day Northwest (18%), Western (18%) and Southern (15%) winds, the average speed of which for the cold period of the year is 3–6 mps, gusts up to 18–20 mps, and during the warm period of the year the average speed is 4–7 mps, gusts up to 20–25 mps.
Keywords: wind direction monitoring; wind velocity; windrose